Affine Variational Inequalities on Normed Spaces - Yen, Nguyen Dong; Yang, Xiaoqi (Journal of optimization theory and applications, 2018)
This paper studies infinite-dimensional affine variational inequalities on normed spaces. It is shown that infinite-dimensional quadratic programming problems and infinite-dimensional linear fractional vector optimization problems can be studied by using affine variational inequalities. We present two basic facts about infinite-dimensional affine variational inequalities: the Lagrange multiplier rule and the solution set decomposition.